Judges' Consideration On Decision Number 582/PDT.G/2019/PN.JKT.TIM Related Legitieme Portie From The Perspective Of The Civil Law Regarding The Division Of Inheritance - Mariana Zhuo; Benny Djaja (Jurnal Jurisprudence, 2023)
ABSTRACT  Purpose: The research aims to determine which comes first and is the higher heir according to law or will on the legal basis of the District Court Judge's Decision Number: 582/PDT.G/2019/PN.JKT.TIM between JM, who sued FN, FTN, AR, and JK. In her case, as the fifth child of the heirs, plaintiff/JM demanded a fair and equitable distribution of inheritance for all the heirs, both sons and daughters, where it turned out that the inheritance was only for daughters in the will. For this reason, this study aims to analyze (1) the basis for Decision Number: 582/PDT.G/2019/PN.JKT.TIM and determine (2) which heir takes precedence based on a will or law. Methodology: The research method used was descriptive analysis, with a normative juridical approach, i.e., library research conducted on secondary data. Results: The study concluded that the consideration of the judge's decision rejected the lawsuit because the lawsuit contained formal defects, was unclear or obscure (obscuur libel), and was unacceptable (Niet Onvantkelijk Verklaard). The selection of heirs based on a will must take precedence by winning the contents and distribution in a will, which is not against the law. The legal consideration is because the will is the testator's last will, but it still conflicts with the absolute portion of the legal property of the testator. Application of this study: This study provides input to readers to better know and understand the rights of heirs in Indonesian laws and regulations. Novelty/Originality of this study: There is a need for outreach to the community, especially couples who are getting married and notaries or related parties, in the event of a purchase or transfer of movable or immovable property which can be inherited. Keywords: Legitime Fortie; Civil law; Inheritance   ABSTRAK Tujuan: Penelitian bertujuan untuk mengetahui ahli waris yang lebih dahulu dan lebih tinggi menurut hukum atau ahli waris menurut wasiat, dengan dasar hukum Putusan Hakim Pengadilan Negeri Nomor: 582/PDT.G/2019/PN.JKT.TIM antara JM, yang menggugat FN, FTN, AR, dan JK. Penggugat/JM, dalam perkaranya sebagai anak kelima ahli waris, menuntut adanya pembagian harta waris yang adil dan merata bagi semua anak ahli waris yang meninggal, baik putra maupun putri, yang ternyata dalam wasiat, harta peninggalan hanya untuk anak perempuan. Oleh karena itu, penelitian ini bertujuan untuk menganalisis (1) dasar putusan Undang-Undang Nomor: 582/PDT.G/2019/PN.JKT.TIM dan mengetahui (2) manakah yang didahulukan antara ahli waris berdasarkan surat wasiat  atau ahli waris berdasarkan undang-undang. Metodologi: Metode penelitian yang digunakan adalah deskriptif-analisis, dengan pendekatan yuridis normatif, yaitu penelitian kepustakaan yang dilakukan terhadap data sekunder. Temuan: Penelitian ini menyimpulkan bahwa pertimbangan putusan hakim menolak gugatan karena gugatan mengandung cacat formil, tidak jelas atau kabur (obscuur libel), dan gugatan tidak dapat diterima (Niet Onvantkelijk Verklaard). Pemilihan ahli waris berdasarkan wasiatlah yang harus didahulukan dengan memenangkan isi dan pembagiannya dalam suatu wasiat yang tidak bertentangan dengan hukum. Pertimbangan hukumnya adalah karena wasiat merupakan wasiat terakhir dari ahli waris tetapi tetap bertentangan dengan pembagian mutlak dari ahli waris yang sah. Kegunaan: Studi ini memberikan masukan kepada pembaca untuk lebih mengetahui dan memahami hak-hak ahli waris dalam peraturan perundang-undangan di Indonesia. Kebaruan/Originalitas: Perlu adanya sosialisasi kepada masyarakat, khususnya pasangan yang akan menikah dan kepada notaris atau pihak terkait, dalam hal terjadi pembelian atau pemindahtanganan barang bergerak atau tidak bergerak yang dapat dijadikan warisan. Kata kunci: Legitime Fortie; Hukum Perdata; Pewarisan